GE_GERICHTE P/6405/2019 vom 17. Februar 2020 - GE Cour de justice (2020)
VIOLATION DE DOMICILE;ACQUITTEMENT;EXPULSION(DROIT PÉNAL);IN DUBIO PRO REO;FIXATION DE LA PEINE;ERREUR SUR LES FAITS(DROIT PÉNAL);RESPONSABILITÉ RESTREINTE(DROIT PÉNAL) | CP.139.al1; CP.186; CP.291; LEI.115.al1.letb; LStup.19.leta; CP.13; CP.66a.al1.letc; CP.66aBis; CP.47; CP.19.al2; LStup.19a.al2